2016
DOI: 10.1530/joe-16-0066
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for regulating seasonal reproduction in vertebrates

Abstract: Animals that inhabit mid- to high-latitude regions exhibit various adaptive behaviors, such as migration, reproduction, molting and hibernation in response to seasonal cues. These adaptive behaviors are tightly regulated by seasonal changes in photoperiod, the relative day length vs night length. Recently, the regulatory pathway of seasonal reproduction has been elucidated using quail. In birds, deep brain photoreceptors receive and transmit light information to the pars tuberalis in the pituitary gland, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 90 publications
0
83
0
Order By: Relevance
“…This endocrine gland is involved in teleost growth and reproduction, through liberation of hormonal stimuli and gonadotropin activation (Falk-Petersen, 2005;Patiño & Sullivan, 2002;Piccinetti et al, 2012;Piferrer & Guiguen, 2008). In addition, development of the saccus vasculosus allowed juveniles to perceive seasonal changes in day length (control of photoperiod) (Nakane et al, 2013;Nishiwaki-Ohkawa & Yoshimura, 2016) and is related to reproduction and growth, influencing the metabolic rate, body pigmentation, behavioural activity and feeding performance (Crovatto-Veras et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This endocrine gland is involved in teleost growth and reproduction, through liberation of hormonal stimuli and gonadotropin activation (Falk-Petersen, 2005;Patiño & Sullivan, 2002;Piccinetti et al, 2012;Piferrer & Guiguen, 2008). In addition, development of the saccus vasculosus allowed juveniles to perceive seasonal changes in day length (control of photoperiod) (Nakane et al, 2013;Nishiwaki-Ohkawa & Yoshimura, 2016) and is related to reproduction and growth, influencing the metabolic rate, body pigmentation, behavioural activity and feeding performance (Crovatto-Veras et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal changes in reproductive physiology mediated by photoperiod in birds and seasonal mammals have been linked to release of thyroid-stimulating hormone from the pars tuberalis of the pituitary gland. This results in conversion within the medio-basal hypothalamus of thyroxine into triiodothyronine (T3) that promotes release of gonadotropin-releasing hormone from neuron terminals in the median eminence (60). It is possible that locally increased tissue concentrations of T3 mediate seasonal cycles in appetite and fat deposition in addition to reproduction.…”
Section: Regulation Of Agrp and Pomc Expression By Incubation Stressmentioning
confidence: 99%
“…Additional environmental factors such as photoperiod, nutrition and temperature also participate in the regulation of seasonal reproductive activity (Estrada-Cortés et al, 2009;Forcada & Abecia, 2006;Rosa & Bryant, 2003). Among these, photoperiod is regarded as the most important factor in the seasonal regulation of reproduction (Menassol, Collet, Chesneau, Malpaux, & Scaramuzzi, 2012;Nishiwaki-Ohkawa & Yoshimura, 2016). Numerous studies have confirmed that seasonal photoperiodic information is conveyed to the pineal gland through the retina.…”
Section: Introductionmentioning
confidence: 99%